No Silver Lining: Evaluating the Need for Consistent and Appropriate Functionality Assessments Among the Increasing and Incarcerated Elderly Population. (December 2020) - Dulisse, Brandon C.; Fitch, Chivon H.; Logan, Matthew
Despite a recent decrease in the U.S. prison population, the proportion of offenders who might classify as elderly has increased exponentially during the same period—the likes of which have created new challenges for administrators tasked with the supervision of, and provision of resources to, this demographic. We review the current literature regarding functionality assessments for elderly inmates to highlight the difficulty associated with using existing instruments that are not specifically designed for the prison setting. We further argue that current efforts to identify elderly inmates are lacking, resulting in the potential misclassification of an already vulnerable group. We propose that future functionality assessments within correctional facilities incorporate a number of age-related factors that focus less on chronological age and more on the mental, physical, and social aging processes of incarcerated individuals.